Titan unveiled Saturn's mysterious moon explored - Lorenz, Ralph 1969-; Mitton, Jacqueline 1948- (Princeton Univ. Press, 2008)
Reveals the startling new discoveries that have been made since the arrival of the Cassini-Huygens mission to Saturn and Titan and offers readers a close-up look at a world that could hold clues to the origins of life on Earth.
Literaturverz. S. 235 - 237
Keywords: Saturn probes; Cassini -- Raumsonde; Titan (Satellite) -- Exploration; Saturn (Planet) -- Satellites; Titan -- Saturnmond